Effect of nursing interventions based on the Kano model on symptom relief and parental psychological behavior in children with febrile seizures - Zhu, Zaiyun; Chen, Liping; Li, Kai (Frontiers in Psychology, 2023)
Purpose To analyze the effect of nursing interventions based on the Kano model on symptom relief and parental psychological behavior in children with febrile seizures (FS). Methods A total of 104 children with FS and their corresponding families admitted to our hospital from January 2021 to April 2022 as the research object. All children were divided into 2 groups according to their nursing regimen during treatment. Children who received general nursing interventions were enrolled in the general group (n = 52) and children who received nursing interventions based on the Kano model were enrolled in the Kano group (n = 52). In this study, an investigation was first conducted to analyze the attributes of the caring care service needs of the families of children with FS. Then, we compared 4 aspects of symptom relief during the hospital stay of the 2 groups of children, including FS seizure frequency, time to cessation of convulsions, time to recovery of consciousness and time to fever reduction. The parent symptom questionnaire (PSQ) was used to assess the psychological behavior of the two groups of children during the hospital stay. The Chinese perceived stress scale (CPSS) and the symptom checklist 90 (SCL-90) were used to assess the psychological behavior of the two groups of their families during the children’s hospitalization. Finally, a questionnaire was administered on the satisfaction of this nursing intervention. Results In terms of symptom relief, the children in the Kano group had less frequent of FS seizure than the general group, and the time to cessation of convulsions, time to recovery of consciousness and time to fever reduction were all earlier than in the genera group (p < 0.05). In terms of children’s psychological behavior, the impulsivity-hyperactivity, anxiety, hyperactivity index and learning problems scores in the PSQ of the children in the Kano group were lower than those in the general group after the intervention (p < 0.05). In terms of family psychological behavior, the psychological behavioral problems of the families of the children in both groups improved after the intervention, and the CPSS scores of tension and dis-control, as well as the total SCL-90 score of the families of the children in the Kano group were lower than those of the general group (p < 0.05). In terms of family satisfaction, the Kano group was significantly better than the general group (p < 0.05). Conclusion The implementation of the nursing interventions based on the Kano model for children with FS was successful in dramatically reducing the clinical signs and symptoms of the children and meeting the psychological and behavioral needs of the children and their families.